Associations between term cesarean delivery in the first pregnancy and second‐pregnancy preterm delivery - Anders Einum; Quaker E. Harmon; Linn Marie Sørbye; Roy Miodini Nilsen; Nils‐Halvdan Morken (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Cesarean delivery has been shown to increase the risk of preterm delivery in future pregnancies. The association could be a direct result of the procedure, or because the indications that led to the cesarean delivery also increase the risk of preterm delivery in later pregnancies. Material and Methods 298 901 mothers with first and second singleton deliveries from 1999 to 2020 were investigated using data from the Medical Birth Registry of Norway linked with Statistics Norway. The mothers were categorized by mode of cesarean delivery (total, emergency and planned) and vaginal delivery at term in the first pregnancy. We used log‐binomial regression models to estimate relative risks with 95% confidence intervals (CI) of iatrogenic and spontaneous preterm delivery <37 gestational weeks in the second pregnancy. Second, we explored the role of recurrent placental disease in preterm delivery by comparing estimates in mothers with placental disease in neither or both pregnancies. Results 8243 mothers (2.8%) had a preterm delivery in the second pregnancy. The adjusted relative risk (aRR) of preterm delivery was 1.24 (95% CI 1.17–1.32) after cesarean compared with vaginal delivery in the first pregnancy. The association was stronger in previous planned compared with emergency cesarean delivery (aRR 1.52, 95% CI 1.30–1.77 and aRR 1.21, 95% CI 1.14–1.29, respectively). Spontaneous preterm delivery was not associated with the previous mode of delivery; the risk was confined to iatrogenic preterm delivery after both emergency and planned cesarean delivery (aRR 1.69, 95% CI 1.52–1.87 and aRR 2.65, 95% CI 2.12–3.30, respectively). Mothers with placental disease in both pregnancies had a sixfold increased risk of preterm delivery in the second pregnancy compared with mothers with no placental disease, however, the association between mode of delivery and subsequent preterm delivery was similar in mothers with and without placental disease in the pregnancies. Conclusions Compared with vaginal term delivery in the first pregnancy, cesarean delivery increases the risk of iatrogenic, but not spontaneous preterm delivery in the next pregnancy. Although strongly associated with preterm delivery, placental disease had limited influence on the estimates.